The Obesity, Metabolic Syndrome, and Type 2 Diabetes Mellitus Pandemic: II. Therapeutic Management of Atherogenic Dyslipidemia - Ginsberg, Henry N. (Blackwell Publishing Ltd, 2009)
Strategies for the effective management of cardiovascular risk factors in patients with the metabolic syndrome (MS) or type 2 diabetes mellitus (T2DM) are essential to help reduce cardiovascular morbidity and mortality. Treatment strategies should be multifactorial and include the promotion of therapeutic lifestyle changes, as well as pharmacologic therapies to treat individual risk factors according to current guidelines. In an accompanying article, the importance of atherogenic dyslipidemia as a risk factor for the development of cardiovascular disease in patients with MS or T2DM was highlighted. Current treatment options for managing this characteristic form of atherogenic dyslipidemia are limited and tend to be only moderately effective. The focus of this review is the current pharmacotherapies available for the management of atherogenic dyslipidemia in patients with the MS or T2DM, highlighting the rationale for combining available treatments. Novel strategies currently in clinical development are also discussed.